Diseño y simulación de un sistema de ducto para la selección y clasificación automática de residuos sólidos generados en edificios residenciales. (2020)
One of the alternatives to mitigate the problem of the impact of solid waste generation is recycling. The solutions that have been proposed to increase recycling in growing cities is separation at the source. In some residential buildings the transport of waste to the deposit is carried out through a pipeline system known as Chute. Although the waste sorting is carried out by residents, these wastes are mixed again in the deposit, generating cleaning problems and reducing recycling at the source of waste generation. This work proposes the design and simulation of a Chute system for automatic selection of solid waste generated in domestic environments. Through the design and programming for its operation, it is intended to solve the problem of waste separation, mainly by depositing the waste in the corresponding container in a way that allows solid waste not to disperse, in the same way a turning mechanism was designed. Four bars to fulfill this function in conjunction with a conveyor belt that will guide a basket placed on it to direct the garbage to the container, in the same way, a diversion is made to the galvanized duct to reduce the speed at which the garbage is untangled.